The genome sequence of the lesser earwig, Labia minor (Linnaeus, 1758) [version 1; peer review: 2 approved] - Mark G. Telfer; Liam M. Crowley (Wellcome Open Research)
We present a genome assembly from an individual male Labia minor (the lesser earwig; Arthropoda; Insecta; Dermaptera; Spongiphoridae). The genome sequence spans 604.50 megabases. Most of the assembly is scaffolded into 7 chromosomal pseudomolecules, including the X sex chromosome. Two mitochondrial scaffolds were also assembled.